Measuring Taxes on Income from Capital: Evidence from the UK - Michael P. Devereux; Alexander Klemm (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper explores the empirical properties of alternative measures of the taxation of income from capital, using UK data over the last thirty years. We analyse measures of effective marginal and average tax rates, based on applying the legal parameters of the tax system to a hypothetical investment; and also measures based on observed tax payments or liabilities, scaled by various measures of income. There is a significant difference between these measures, both in their level and in how they move over time. The implicit assumption in some empirical work that these measures are broadly comparable to each other is not justified.
Keywords: 330